Proton pump inhibitors use and change in bone mineral density. (31st May 2016) - Arj, Abbas; Razavi Zade, Mohsen; Yavari, Maryam; Akbari, Hossein; Zamani, Batol; Asemi, Zatollah
Abstract: Objective: Limited data are available reporting the effect of proton pump inhibitor (PPI) use on changes in bone mineral density (BMD). The aim of this study was to investigate the relationship between PPI use and BMD. Methods: The current cross‐sectional study included 80 patients (31 male and 49 female) aged 20–45 years old without history of hip fracture with a follow‐up of at least 2 years. The study was carried out in 40 daily PPI users and 40 PPI non‐users. Femur and posterior‐anterior spine BMD were quantified by dual‐energy X‐ray absorptiometry in all participants. The relationship between use of PPI and BMD was tested by multivariate linear regression analysis adjusted for age, sex, BMI and serum vitamin D levels. Results: Our study demonstrated that mean femoral T ‐scores were significant between PPI and non‐user groups (−0.44 ± 1.11 vs . +0.19 ± 0.95, P = 0.007). In addition, the frequency of femoral osteoporosis and osteopenia in the exposed group was significantly more in the control group ( P = 0.04). Mean femoral Z ‐scores, lumbar spine T ‐score and lumbar spine Z ‐score were not statistically different between PPI and non‐user groups. The linear regression analysis revealed that there was no association between PPI and non‐users, and lumbar spine T ‐score. Conclusion: Overall, the results of this study showed that PPI use in subjects without risk factors of osteoporosis determined by the femoral T ‐score compared with the control group was associated with increased risk of developing osteoporosis and osteopenia in the femur bones.